Modelling and Transactional Analysis of an Omni-directional Mobile Manipulating Robot - Ding Xiaojun; Ma Qin; Zhao Tao; Liu Feng; Hu Xin (Jixie chuandong)
The omni-directional mobile manipulator robot (OMMR) is a class of a new robot with activating operating capability, which is composed of one or more manipulators mounted on a mobile platform. However, after the manipulator is installed on the mobile platform, the coupling effect between the manipulator and the mobile platform will significantly increase the complexity of the dynamic behavior of the whole system, involving the dynamic interaction between the ground and the mobile platform, the mobile platform and the manipulator, the manipulator and the operating environment, which brings great difficulties to the modeling of the system. Based on establishing the kinematics and statics models of OMMR, this study presents a simplified modeling approach of OMMR system dynamics. Based on this dynamic model, the vehicle-manipulator interaction model is established, and its interaction is analyzed. Simulation and experiments verify the correctness of the vehicle-manipulator interaction model, indirectly prove the rationality and effectiveness of the proposed OMMR system dynamics modeling approach, and provide model data for motion planning and control of robots.